Mitigation Interventions in the United States: An Exploratory Investigation of Determinants and Impacts. (January 2021) - Guo, Shenyang; An, Ruopeng; McBride, Timothy D.; Yu, Danlin; Fu, Linyun; Yang, Yuanyuan
Purpose: To examine the determinants and impacts of implementing the mitigation interventions to combat the COVID-19 disease in the United States during the first 5 weeks of the pandemic. Method: A content analysis identified nine types of mitigation interventions and the timing at which states enacted these strategies. A proportional hazard model, a multiple-event survival model, and a random-effect spatial error panel model in conjunction with a robust method analyzing zero-inflated and skewed outcomes were employed in the data analysis. Findings: Contradictory to the study hypothesis, states initially with a high COVID-19 prevalence rate enacted mitigation strategies slowly. Three mitigation strategies (nonessential business closure, large-gathering bans, and restaurant/bar limitations) showed positive impacts on reducing cumulative cases, new cases, and death rates across states. Conclusion: Some states may have missed optimal timing to implement mitigations. Swift implementation of mitigations is crucial. Reopening economy by fully lifting mitigation interventions is risky.